Land Control and Ideological Struggle: Competing Articulations of â€œThe Owner of Landâ€ - Savitri, Laksmi Adriani (Journal of Rural Indonesia [JORI], 2013)
The implementation of large scale industrial farming investment involves land deals that are not only being navigated through regulated practices, but state and non-state actors also employ a strategy to ‘grip the minds of the masses’ to enable the deals. ‘Gripping the minds’ involves articulatory practices within the terrain of ideological struggle, which put land deals always in process. This paper argues that ‘the owner of land’ as a cultural identity that was constructed historically by determining forces, and not confined merely as form of rights, is articulated in three competing positionings toward land deals: rejection, renegotiation and acceptance. The state and non-state actors or NGOs broker the process of identification toward modernism by constructing representations of capital as the good and bad Other. These representations of capital provide ‘logic’ which connected meanings of modernism with ‘the owner of land’ identity. ‘Gripping the mind of the masses’ to smoothen land deals involves correspondences as well as non-correspondences between modernism and the Marind identity of Anim-ha that render connected chain of meanings unstable. © 2013 Journal of Rural Indonesia [JoRI] IPB. All rights reserved. Keyword: land control, land deals